2020
DOI: 10.26444/aaem/123107
|View full text |Cite
|
Sign up to set email alerts
|

Importance of food allergy and food intolerance in allergic multimorbidity

Abstract: Introduction. Allergy affects approximately one-third of the world's population, and the rates are growing. In Europe, it has been noticed that the risk of asthma and allergy is lower in the rural as opposed to urban population. There is a tendency for several allergic diseases to be present in the same person at the same time. Objective. The aim of the study was to verify the co-occurrence of allergic multimorbidity and food allergy and intolerance in a group of children. Materials and method. The multicentre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…In the epidemiological study, allergic rhinitis occurred in 46.4%, asthma was in 11.2 %, and allergic multimorbidity was diagnosed in 9.7% compared with a single allergic disease in 43.4%. The current study's findings indicated an association between food allergies and the presence of at least one allergic disease [43].…”
Section: Co-influence Of Respiratory and Food Allergiessupporting
confidence: 52%
“…In the epidemiological study, allergic rhinitis occurred in 46.4%, asthma was in 11.2 %, and allergic multimorbidity was diagnosed in 9.7% compared with a single allergic disease in 43.4%. The current study's findings indicated an association between food allergies and the presence of at least one allergic disease [43].…”
Section: Co-influence Of Respiratory and Food Allergiessupporting
confidence: 52%
“…Allergic multimorbidity studies including FA are lacking. However, a Polish multicentre cross‐sectional study on children and adolescents (age range 6–18 years) reported that FA is more frequent in children with allergy multimorbidity (other variables: AS, AD, AR) than those with one allergic disease 29 . In addition, multimorbidity in early life and food‐related symptoms in later life have been indicated to have a strong association.…”
Section: Discussionmentioning
confidence: 99%
“…The Finnish Medical Foundation; The Research Foundation of the Pulmonary Diseases; The Finnish National Allergy Programme; The Ida-Montini Foundation; The Research Foundation of Väinö and Laina Kivi; The Association of Finnish Pharmacies; The Foundation of the Finnish Anti-Tuberculosis Association; The Finnish Society of Allergology and Immunology reported that FA is more frequent in children with allergy multimorbidity (other variables: AS, AD, AR) than those with one allergic disease. 29 In addition, multimorbidity in early life and food-related symptoms in later life have been indicated to have a strong association. Adolescents with anaphylaxis have more frequently exhibited polysensitization, including for example, several foods and nut storage proteins when compared with adolescents without anaphylaxis.…”
Section: Funding Informationmentioning
confidence: 99%
“…The mechanism of immune oral tolerance has not been elucidated, but it is clear that it may be disrupted in multiple stages. When enzymatic disruption of conformational epitopes in potential food allergens is reduced, epithelial cells secrete inflammatory cytokines such as IL-25 and IL-33 to inhibit IL-12 production [ 5 , 59 ]. In this condition, DCs and other antigen-presenting cells are activated and transformed into a functional pro-inflammatory phenotype.…”
Section: The Role Of Selenoproteins In the Prevention Of Food Allergiesmentioning
confidence: 99%